Structural Studies of ZnS Nanoparticles by High Resolution Transmission Electron Microscopy - Oliva, A.I.; Zavala, G.; Gayou, V.L.; Salazar Hernández, B.; Delgado Macuil, R.; Santiago, P. (Journal of nano research, 2010)
Zinc sulfide (ZnS), a representative of wide band gap semiconductor nanocrystals, has an excitonic Bohr radius (aBZnS ) of 2.5 nm. It makes ZnS nanoparticles (ZnS NP) having such size very interesting as small biomolecular probes for fluorescence and laser scanning microscopy. To date, ZnS NP of diameters larger than aBZnS has been subject of extensive experimental and theoretical studies. However many questions remain open concerning the synthesis of undoped and uncapped ZnS NP of diameters less than 2.5 nm. To further probe into the physical properties of undoped and uncapped ZnS NP, in this work we report on studies of uncapped ZnS nanoparticles synthesized by a wet chemical process at room temperature. Three colloidal suspensions (named A, B and C, respectively) were obtained from 9:1, 1:1 and 1:9 volume mixtures of 1mM ZnSO4 and 0.85mM Na2S aqueous solutions. Qualitative differences in UV-Vis absorption spectra are discussed in the context of Z-contrast scanning transmission electron microscopy (Z-contrast), low and high resolution transmission electron microscopy (TEM) results. Distribution of particle size is dependent on different volumes of source solutions. For the intermediate mixture, it has been found that about 78% of ZnS nanoparticles have a diameter smaller than the excitonic Bohr Radius of 2.5 nm. HRTEM studies have revealed that nanoparticles grow preferentially with hexagonal structure.